Assessing the Impact of IT, Trade Globalisation, and Economic Complexity on Carbon Emissions in BRICS Economies - Tuba Rasheed; Hamza Akram; Mahwish Zafar; Md Billal Hossain (Economies, 2025)
The escalating threat of climate change has placed carbon dioxide (CO2) emissions at the forefront of global environmental policy. The relationship between carbon dioxide (CO2) emissions and information technology (IT) is crucial in shaping international climate change strategies. This study investigates the impact of information technology, trade globalisation (TG), and economic complexity (EC) on CO2 emissions in BRICS countries using panel data from 1996 to 2018. The analysis applies the CUP-FM estimator to assess long-run relationships and the Dumitrescu–Hurlin panel causality test to evaluate directionality. The results show that information technology significantly reduces CO2 emissions. This effect is primarily driven by the promotion of the service sector, reduced material use, and improved energy efficiency. In contrast, trade globalisation has an inconsistent impact. While it can lower emissions through technology diffusion and efficiency gains, it can also increase them due to Scale Effects and the relocation of polluting industries. This study also identifies a U-shaped relationship between economic complexity and CO2 emissions, indicating that emissions initially rise with complexity but decline as innovation and clean production practices improve. These findings suggest that developing digital infrastructure and green technologies and trade Globalisation can promote sustainable development in BRICS economies. Therefore, policymakers should prioritise strengthening the IT environment, fostering international trade partnerships, and integrating clean technologies to balance economic growth with environmental protection.